Nano-silver sintering packaging process and structure of high-power module

CN123022274APending Publication Date: 2026-10-30HEFEI ZHONGHENG MICRO SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611509935.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明要解决现有大功率半导体模块纳米银烧结封装中存在的两方面技术问题

Benefits of technology

[0012]本发明将上述结构与工艺协同配合,使结构中不同功能单元分别在工艺的不同阶段发挥相应作用,能够将烧结互连层的孔隙率降低至10%以下,并将焊盘边缘的剪切应力峰值降低30%以上,显著提升大功率碳化硅、氮化镓模块在多芯片同板烧结及极端热冲击工况下的封装良率与循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022274A_ABST
    Figure CN123022274A_ABST
Patent Text Reader

Abstract

The application discloses a nano-silver sintering packaging process and structure of a high-power module, and relates to the technical field of semiconductor power module packaging. The structure is provided with an array type micro neck copper column, a radiation micro groove network and a limiting resistance welding dam on a patterned copper pad of a ceramic copper clad substrate. The micro neck copper column generates controllable axial plastic deformation at the necking section when the yield pressure is exceeded to compensate for the multi-chip thickness tolerance. The radiation micro groove network provides a directional discharge channel for volatile organic compounds in the center area of the pad. The limiting resistance welding dam guides the edge silver paste to form a crescent structure to release stress concentration. The matched sintering process is first low-temperature vacuum degassing, and then high-temperature positive pressure densification. The application can reduce the sintering porosity and the edge shear stress peak value, improve the packaging reliability of the high-power semiconductor module, and is suitable for the interconnection packaging of high-power chips.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor power module packaging technology, specifically to the nano-silver sintering packaging process and structure for high-power modules. Background Technology

[0002] Nano-silver sintering technology utilizes the characteristics of small particle size and high surface energy of nano-silver particles to achieve neck growth and densification between particles through atomic surface diffusion at temperatures far below the melting point of silver, forming a metal interconnect layer with high thermal conductivity and high electrical conductivity. The thermal conductivity of this interconnect layer can exceed 200 watts per meter Kelvin, and its melting point is much higher than that of traditional lead-containing solder. It is considered an ideal solution for interconnecting high-power semiconductor module chips and has been widely used in the chip mounting field.

[0003] In the prior art, power chips are usually mounted on continuous flat pads on a ceramic copper-clad substrate. The back side of the substrate is usually connected to a heat sink or water-cooling plate to form a power module structure with single-sided or double-sided heat dissipation. A flexible polymer buffer pad is placed between the sintering head and the chip to absorb the thickness difference between the chips when multiple chips are sintered on the same board. Then, the chips are sintered in one go under a constant axial pressure of 10 MPa to 30 MPa in a vacuum chamber at 200°C to 300°C.

[0004] The existing solution has the following shortcomings: the flexible buffer pad is prone to viscoelastic rheology under high temperature and high pressure, and cannot maintain uniform support force for a long time, which leads to lateral slippage of the chip. It is difficult to solve the contradiction between chip thickness tolerance and uniform pressure from the structural source. At the same time, the surface of the pad is a continuous plane without a guiding structure. When large-area chip sintering, the edge silver paste preferentially densifies to form a gas barrier, which makes it difficult for volatile organic compounds in the central area of ​​the chip to be discharged, forming voids. In addition, the right-angle structure of the pad edge and the difference in thermal expansion coefficient between the chip cause stress concentration. The above problems are coupled with each other, which further limits the service life of high-power modules under extreme thermal shock conditions.

[0005] Therefore, how to simultaneously achieve adaptive compensation of thickness tolerance of multiple chips and effective venting of the central area of ​​large-area chips within the same packaging system has become a key problem that needs to be solved in the nano-silver sintering packaging of high-power modules. Summary of the Invention

[0006] This invention aims to solve two technical problems existing in the current nano-silver sintering packaging of high-power semiconductor modules.

[0007] Firstly, in the scenario of sintering multiple chips on the same board, each chip has its own thickness and manufacturing tolerances. However, the existing technology applies a constant axial pressure to all chips, causing the actual pressure on thicker chips to be significantly higher than the design value, resulting in stress concentration or even breakage. Thinner chips, on the other hand, fail to achieve sufficient densification of the nano-silver particles due to insufficient pressure, resulting in poor soldering. The polymer flexible buffer pads used in the existing technology are prone to viscoelastic rheology under high temperature and high pressure conditions, making it impossible to maintain uniform support force for a long time. This can also cause lateral slippage of the chips, making it difficult to resolve the contradiction between chip thickness tolerance and uniform pressure from the structural source.

[0008] Secondly, in large-area chip sintering scenarios, the edge area of ​​the pads is preferentially heated and densified due to the shorter heat dissipation path, forming a dense barrier wall around the chip. This prevents volatile organic solvents and dispersant gases in the central area of ​​the chip from being discharged smoothly, forming macroscopic voids inside the interconnect layer. At the same time, the difference in thermal expansion coefficients between the substrate and the chip causes stress concentration at the right-angle structure of the pad edge. The void defects and edge stress concentration are superimposed, further deteriorating the reliability of the module under temperature cycling conditions.

[0009] To address the aforementioned issues, this invention provides a nano-silver sintered packaging structure for high-power modules, comprising a ceramic copper-clad substrate, patterned copper pads disposed on the surface of the ceramic copper-clad substrate, a nano-silver paste layer coated on the surface of the patterned copper pads, and a power chip mounted on the nano-silver paste layer. The surface of the patterned copper pads is provided with an array of multiple micro-necked copper pillars. Each micro-necked copper pillar includes a lower base section, a necked section, and an upper base section sequentially from bottom to top along the axial direction. The cross-sectional area of ​​the necked section is smaller than the cross-sectional areas of the lower base section and the upper base section, enabling the micro-necked copper pillar to undergo controllable axial plastic compression deformation in the necked section when subjected to axial pressure exceeding the yield pressure of the necked section. This achieves adaptive compensation of the chip thickness tolerance of the all-inorganic pure metal material, eliminating the need for polymer buffer materials that are prone to high-temperature rheology.

[0010] A radial microgroove network is provided in the gap area between adjacent micro-necked copper pillars. The radial microgroove network includes multiple microgrooves that extend radially outward from the center of the patterned copper pad. The outer end of each microgroove is connected to an annular gas collection groove located around the patterned copper pad, and then connected to the vacuum extraction passage of the sintering equipment. This provides a directional and interconnected low-resistance exhaust path for the organic gases volatilized in the center area of ​​the pad. A limiting solder resist dam is provided circumferentially around the patterned copper pad. The inner wall of the limiting solder resist dam forms an angle of 30° to 45° with the plane where the patterned copper pad is located. This is used to limit the lateral overflow range of the nano silver paste during the heated flow stage and guide the edge silver paste to climb up the inclined wall. After cooling and solidification, it forms a concave meniscus structure with a rounded transition, which alleviates the stress concentration at the edge.

[0011] The present invention also provides an in-situ vacuum-positive pressure gradient sintering process that is compatible with the above structure. In this process, the cavity is heated to a first temperature and a vacuum micro-pressure is applied and maintained for a first time in the same sintering equipment cavity without changing the workpiece, so that the organic gas volatilized in the chip area is directionally discharged through the radiation micro-groove network and the annular gas collection groove. The cavity is then heated to a second temperature, and the application method is switched from vacuum micro-pressure to positive pressure loading. This is maintained for a second time, so that the necked section of the micro-necked copper pillar undergoes axial plastic compression deformation under pressure to compensate for the thickness tolerance between multiple chips. At the same time, the nano silver paste layer is accelerated to densify and forms a concave meniscus structure under the constraint of the limiting solder resist dam. Finally, the module substrate was cooled and depressurized according to the preset cooling curve, and then removed after sintering.

[0012] This invention combines the above-mentioned structure and process in a coordinated manner, so that different functional units in the structure play their respective roles at different stages of the process. It can reduce the porosity of the sintered interconnect layer to below 10% and reduce the peak shear stress at the edge of the pad by more than 30%, significantly improving the packaging yield and cycle life of high-power silicon carbide and gallium nitride modules under multi-chip sintering and extreme thermal shock conditions. Attached Figure Description

[0013] Figure 1 A cross-sectional view of the existing planar pad flexible buffer pad sintering scheme; Figure 2 This is a top view of the composite microstructure in the pad area of ​​the present invention. Figure 3 This is a cross-sectional view of the micro-neck copper pillar structure of the present invention; Figure 4 This is a timing diagram of the vacuum-positive pressure gradient synergistic sintering process of the present invention. Detailed Implementation

[0014] The following is in conjunction with the appendix Figure 1-4 The specific embodiments of the present invention will be further described below. It should be noted that the description of these embodiments is for the purpose of helping to understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0015] I. Composite substrate structure The high-power module nano-silver sintered packaging structure provided in this embodiment includes a ceramic copper-clad substrate 10, patterned copper pads 20, a nano-silver paste layer 60, and a power chip 70. The ceramic copper-clad substrate 10 is a direct-bonded copper substrate or an active metal brazing substrate, including a ceramic base and copper-clad layers respectively disposed on the upper and lower surfaces of the ceramic base. The material of the ceramic base can be alumina, aluminum nitride, or silicon nitride. The thickness of the copper-clad layer is about 0.2 mm to 0.5 mm. The patterned copper pads 20 are processed by a patterning process from the copper-clad layer on the upper surface of the ceramic copper-clad substrate 10. The nano-silver paste layer 60 is coated on the surface of the patterned copper pads 20. The power chip 70 is mounted on the nano-silver paste layer 60. The power chip 70 is a silicon carbide or gallium nitride power chip. The back side of the ceramic copper-clad substrate 10 can also be connected to a heat sink or a water-cooling plate to form a power module structure with single-sided or double-sided heat dissipation.

[0016] The nano-silver paste used in the nano-silver paste layer 60 is composed of nano-silver particles, organic dispersants and organic solvents. The nano-silver particles have a particle size of about 20 nanometers to 100 nanometers and their mass proportion in the silver paste is about 80% to 90%. The organic dispersants and organic solvents are used to ensure the fluidity of the silver paste during the printing or dotting process and are evaporated by heat during the subsequent degassing stage.

[0017] Three types of collaborative microstructure units are constructed on the surface of the patterned copper pad 20, namely micro-necked copper pillars 30, radiating micro-groove network 40, and limiting solder resist dam 50.

[0018] Micro-necked copper pillars 30 are arranged in an array on the surface of patterned copper pads 20. They can be grown on the pad surface using photolithography combined with micro-electroplating, or they can be formed by directly etching the copper-clad layer using a picosecond laser. Each micro-necked copper pillar 30 includes, from bottom to top along the axial direction, a lower base section 31, a necked section 32, and an upper base section 33. The lower base section 31 is integrally connected to the patterned copper pads 20, and the upper base section 33 is in contact with the nano-silver paste layer 60. The cross-sectional area of ​​the necked section 32 is... The cross-sectional area is significantly smaller than that of the lower base section 31 and the upper base section 33. In this embodiment, the diameter of the lower base section 31 is approximately 200 to 300 micrometers, the diameter of the necked section 32 is approximately 60 to 120 micrometers, the diameter of the upper base section 33 is approximately 200 to 300 micrometers, the total height of the micro-necked copper pillars 30 is approximately 150 to 300 micrometers, and the center-to-center distance between adjacent micro-necked copper pillars 30 is approximately 300 to 600 micrometers. Due to the necking... The cross-sectional area of ​​segment 32 is smaller, and its equivalent stress under axial pressure is significantly higher than that of the lower base segment 31 and the upper base segment 33. When the applied axial pressure exceeds the yield pressure of the material of the necked segment 32, the necked segment 32 preferentially undergoes controllable axial plastic compression deformation, while the lower base segment 31 and the upper base segment 33, due to their larger cross-sectional area and equivalent stress below the yield threshold, remain basically undeformed. This concentrates the deformation in a pre-designed local area, achieving predictable and controllable axial compression compensation. In one implementation of this embodiment, the contour of the necked segment 32 first contracts and then expands from the lower base segment 31 to the upper base segment 33, making the micro-necked copper column 30 have a dumbbell-shaped contour. This contour is conducive to the uniform bulging plastic deformation of the necked segment 32 under pressure, avoiding deformation concentration in a single section and causing local tearing. The material of the micro-necked copper column 30 can be oxygen-free copper or pure copper, and the yield strength after annealing is about 50 MPa to 80 MPa.

[0019] During the compensation and densification stage, the relationship between the axial plastic compression generated by the necked section 32 of the micro-necked copper column 30 and the applied pressure can be approximated by the following simplified mechanical model: ; In the formula, The value represents the axial plastic compression generated by the necked section 32 of the micro-necked copper pillar 30, expressed in micrometers. This indicates the sintering positive pressure applied during the compensation and densification stages, expressed in megapascals (MPA). This indicates the yield strength of the 32 material in the necked section, expressed in megapascals (MPa). This represents the cross-sectional area of ​​the necked section 32, in square millimeters. This represents the equivalent stiffness coefficient of the necked section 32 during the plastic deformation stage. This coefficient is determined by the geometry and material properties of the necked section 32, and is expressed in Newtons per micrometer. When pressure is applied... Yield strength exceeding 32 mm in the necked section At the corresponding critical pressure, the necked section 32 produces the controllable plastic compression described in the above formula. Under the vacuum micro-pressure conditions applied during normal service and exhaust stages, the pressure is lower than the critical pressure, and the micro-necked copper column 30 remains rigid and basically does not deform, thereby ensuring the support stability of the structure in the non-compensation stage.

[0020] In multi-chip sintering scenarios, the compression difference generated by the micro-neck copper pillars 30 array beneath chips of different thicknesses is used to smooth out the original thickness tolerance between chips. The relationship can be expressed as: ; In the formula, This indicates the original thickness tolerance between the two power chips 70, in micrometers. The value represents the axial compression caused by the array of micronecked copper pillars 30 beneath the relatively thick power chip 70, expressed in micrometers. The value represents the axial compression generated by the array of micro-necked copper pillars 30 below the thinner power chip 70, expressed in micrometers. Because the thicker power chip 70 experiences higher local pressure under a uniformly applied positive pressure, its necked section 32 reaches the yield threshold and generates a greater axial compression than the necked section 32 below the thinner power chip 70. This is within the original thickness tolerance. When within the pre-designed compensation range of the micro-neck copper column 30 structure and The difference can automatically offset the height difference of the top surfaces of the two power chips 70 after installation, so that the effective pressure actually borne by the two power chips 70 during the densification stage tends to be consistent, thereby avoiding the thicker chip from cracking due to stress concentration and the thinner chip from being poorly soldered due to insufficient pressure.

[0021] The radial microgroove network 40 is disposed in the gap region between adjacent micro-necked copper pillars 30. It can be formed simultaneously using the same photolithography or laser process as the micro-necked copper pillars 30, thereby reducing the number of manufacturing steps. The radial microgroove network 40 includes multiple microgrooves 41. Each microgroove 41 extends radially outward from the center of the patterned copper pad 20 as the origin. The width of the microgrooves 41 is approximately 10 micrometers to 30 micrometers, and the depth is approximately 5 micrometers to 20 micrometers. The outer end of each microgroove 41 is connected to an annular gas collection groove 42 disposed around the patterned copper pad 20. The annular gas collection groove 42 is further connected to the vacuum extraction passage of the sintering equipment cavity, thereby forming a low-resistance exhaust path that runs through the center of the patterned copper pad 20 to the external vacuum system.

[0022] During the exhaust phase, the volumetric flow rate of the gas within a single microgroove 41 can be represented using the Poiseuille flow approximation model: ; In the formula, This represents the volumetric flow rate of gas within a single microgroove 41, expressed in cubic meters per second. This represents the equivalent hydraulic radius of the cross-section of microgroove 41, in meters. This represents the pressure difference between the two ends of the micro-trench 41, i.e., the central region of the power chip 70, and the surrounding vacuum extraction port. This pressure difference is provided by the vacuum system of the sintering equipment, and the unit is Pascal. The dynamic viscosity of volatile organic gases, expressed in Pascals per second (Pa·s). This represents the path length of the microtrench 41 from the center of the patterned copper pad 20 to the outer vent, in meters. From the above formula, it can be seen that under vacuum conditions... and trench length Under certain conditions, the equivalent hydraulic radius of the micro-groove 41 Since the exhaust flow rate is sensitive to the fourth power, this invention can achieve an exhaust efficiency far higher than that of a continuous planar pad structure within a limited pad area by rationally designing the cross-sectional dimensions of the radial micro-trench network 40. This fundamentally avoids macroscopic void defects caused by exhaust obstruction in the central area of ​​the large-area power chip 70.

[0023] The limiting solder resist dam 50 is continuously arranged circumferentially around the patterned copper pad 20, and has a raised structure. Its inner sidewall forms an angle between 30° and 45° with the plane of the patterned copper pad 20. During the heated flow stage of the nano-silver paste layer 60, the limiting solder resist dam 50 physically restricts the lateral flow range of the nano-silver paste layer 60, preventing the silver paste from overflowing outside the pad area. Simultaneously, after softening upon heating, the silver paste in the edge area slopes upwards along the angled inner sidewall of the limiting solder resist dam 50. As the temperature rises... Under pressure, the edge silver paste gradually densifies and naturally forms a concave meniscus structure with a rounded transition after cooling and solidification. Compared with the right-angle edge structure, this concave meniscus structure can effectively reduce the stress concentration caused by the difference in thermal expansion coefficients between the silver paste edge and the power chip 70 and the patterned copper pads 20. The height of the limiting solder resist dam 50 is about 20 micrometers to 50 micrometers, which can be processed synchronously with the micro-necked copper pillars 30 and the radiating micro-groove network 40 using the same photolithography or laser process, without the need for additional manufacturing processes.

[0024] When fabricating the micro-necked copper pillars 30, the radiating micro-groove network 40, and the limiting solder resist dam 50 using a photolithography combined with micro-electroplating, photoresist can be sequentially coated onto the surface of the patterned copper pads 20. Through exposure and development, a patterned mask corresponding to the outlines of the micro-necked copper pillars 30 array, the micro-grooves 41, and the limiting solder resist dam 50 is formed. Subsequently, a copper layer is grown in the opening area of ​​the mask through an electroplating process. After multiple cycles of photoresist coating, exposure, development, and electroplating, the lower base section 31, the necked section 32, and the upper base section are gradually formed. The three-segment outline of 33 is then removed, and the photoresist mask is removed to complete the integrated fabrication of the microstructure unit. When fabricating using picosecond laser direct etching, the outline of the radiating micro-groove network 40 between the micro-necked copper pillars 30 array and the limiting solder resist dam 50 can be directly etched on the surface of the patterned copper pad 20 by adjusting the laser power density, scanning path and scanning number, while keeping the copper pillar array area unetched. Thus, the processing of three types of microstructure units can be completed simultaneously in a single process, improving manufacturing efficiency.

[0025] II. In-situ vacuum-positive pressure gradient sintering process After completing the preparation of the above-mentioned composite substrate structure, the present invention further provides a two-stage synergistic sintering process.

[0026] First, the ceramic copper-clad substrate 10, which has been constructed with micro-necked copper pillars 30, radiating micro-groove network 40 and limiting solder resist dam 50, is cleaned and surface activated. Then, nano silver paste is printed or dotted on the surface of patterned copper pads 20 to form nano silver paste layer 60. The thickness of nano silver paste layer 60 is preset according to the specifications of power chip 70.

[0027] Then, the power chips 70 to be packaged are mounted one by one on the nano silver paste layer 60 of the corresponding patterned copper pads 20 to complete the overall arrangement of the multi-chip array, and preliminary positioning and curing treatments such as low-temperature pre-drying are performed to prevent the power chips 70 from shifting during subsequent handling.

[0028] Next, the ceramic copper-clad substrate 10, after being mounted, is placed into the vacuum nano-silver sintering press chamber. The chamber temperature is raised to a first temperature, which is approximately 150°C, below the temperature threshold for the drastic densification of nano-silver particles. Simultaneously, a vacuum micro-pressure is applied to the chamber, with the absolute pressure controlled at a low level and maintained for a first time, which is 20 minutes. During this stage, the radiating micro-groove network 40 establishes a low-resistance gas path between the center of the patterned copper pads 20 and the peripheral vacuum system. This allows the organic solvent and dispersant gases volatilized in the central region of the power chip 70 to be quickly and unobstructedly discharged along the micro-grooves 41, fundamentally preventing the gas in the central region from being sealed and encased by the edge dense layer.

[0029] Subsequently, the cavity temperature is further increased to a second temperature, which is not lower than 250°C. At the same time, the application method is switched from vacuum micro-pressure to positive pressure loading. The applied positive pressure is about 15 MPa, which can be adjusted within the range of 10 MPa to 20 MPa according to the specific power chip 70 and silver paste formula, and is maintained for a second time of 30 minutes. During this stage, the micro-necked copper pillars 30 array below the thicker power chip 70 reaches the yield threshold of the necking section 32 before the micro-necked copper pillars 30 array below the thinner power chip 70 due to the higher local pressure, resulting in axial plastic compression deformation. This automatically reduces the relative height of the top surface of the power chip 70, making the effective pressure of multiple power chips 70 in the array tend to be balanced. At the same time, the nano silver paste layer 60 accelerates densification under the combined action of positive pressure and temperature, and is distributed along the inclination angle of its inner wall under the geometric constraint of the limiting solder resist dam 50, forming an arc-shaped concave meniscus structure.

[0030] Finally, after the second time of the compensation and densification stage, the cavity temperature is gradually reduced to room temperature according to the preset cooling curve, and the positive pressure is gradually released to normal pressure. Then, the sintered module substrate is taken out from the press cavity. The sintered module is subjected to appearance inspection, X-ray porosity detection and necessary electrical and thermal performance tests. Unqualified products are rejected and qualified products enter the subsequent packaging process.

[0031] The sintering equipment cavity is also equipped with a temperature control device and a pressure control device. The temperature control device is used to heat and control the cavity according to the preset heating, holding and cooling curves. The pressure control device is used to apply a vacuum micro-pressure during the exhaust stage, switch to positive pressure loading during the compensation and densification stage, and gradually release the pressure to normal pressure during the cooling stage. The vacuum pumping passage is connected to a vacuum pump outside the cavity to continuously extract the volatile organic gases collected by the annular gas collecting groove 42 from the cavity, so as to avoid the accumulation of gas in the cavity and affect the sintering quality.

[0032] III. Mechanism of Structural and Technological Synergy The three types of microstructure units in the composite substrate structure of the present invention play a major role in different stages of the synergistic sintering process: In the venting stage, the radial microgroove network 40 provides a directional venting channel for volatile organic compounds in the central area of ​​the pads, while the micro-necked copper pillars 30 and the limiting solder resist dams 50 remain in their initial state because the pressure they are subjected to is lower than their respective functional thresholds. In the compensation and densification stage, the necked section 32 of the micro-necked copper pillars 30 undergoes controllable axial plastic deformation to compensate for the thickness tolerance of the multi-chip, and the limiting solder resist dams 50 guide the edge silver paste to form a concave meniscus structure to alleviate stress concentration. The radial microgroove network 40 is gradually filled due to the densification of the silver paste and no longer serves as the main venting channel. The three types of microstructure units and the two-stage sintering process cooperate with each other in a predetermined sequence, so that different functional units in the structure play their roles in different stages of the process, realizing the integrated synergy of structure and process.

[0033] IV. Alternative Implementation Methods In another embodiment of the present invention, the micro-necked copper pillar 30 can also be replaced by a micro-spring-shaped copper pillar with a spiral shape instead of the aforementioned dumbbell-shaped necking structure. The elastic deformation of the spiral structure itself, rather than plastic deformation, is used to absorb the thickness tolerance of the power chip 70. This embodiment has the advantages of deformation recovery and is not prone to permanent damage, and is suitable for application scenarios with high requirements for the number of sintering pressure cycles.

[0034] In another embodiment of the present invention, the radial microgroove network 40 can also be designed as a grid-like composite trench network that combines radial extension and circumferential connection to further improve the uniformity of the exhaust path coverage in the pad area.

[0035] In another embodiment of the present invention, the limiting solder resist dam 50 can also be designed as a structure that is segmented along the circumference of the patterned copper pad 20. For power chips 70 with asymmetrical shapes or asymmetrical layouts, dam segments with different inclination angles are set at different positions of the patterned copper pad 20 to adapt to the edge stress relief requirements in complex chip layout scenarios.

[0036] V. Effect Verification In one specific embodiment, two silicon carbide power chips 70 to be sintered on the same board are packaged, wherein the thickness of the first power chip 70 is approximately 8 micrometers larger than that of the second power chip 70. After the two power chips 70 are respectively mounted on the nano-silver paste layer 60 of the corresponding patterned copper pads 20, a positive pressure of 15 MPa is applied during the compensation and densification stage, and the chip is held at 250°C for a predetermined time. The local pressure borne by the micro-necked copper pillars 30 array below the first power chip 70 is higher than that below the second power chip 70. Its necked section 32 reaches the yield threshold first and generates an axial compression of approximately 8 micrometers. The axial compression generated by the array of micro-necked copper pillars 30 below the power chip 70 is significantly smaller. The difference in compression between the two is basically equivalent to the original thickness tolerance, making the effective pressure actually borne by the two power chips 70 tend to be consistent during the densification stage. After testing, the interconnect layer thickness of the two power chips 70 is uniform and the porosity is less than 10% after sintering. No cracking or poor soldering is observed. Temperature cycle reliability testing was performed on the sintered module. The peak shear stress in the pad edge area was reduced by more than 30% compared to the existing planar pad flexible buffer pad solution. The cycle life of the module under extreme thermal shock conditions is significantly improved.

[0037] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope defined by the claims of the present invention.

Claims

1. A nano-silver sintered packaging structure for a high-power module, comprising a ceramic copper-clad substrate, patterned copper pads disposed on the surface of the ceramic copper-clad substrate, a nano-silver paste layer coated on the surface of the patterned copper pads, and a power chip mounted on the nano-silver paste layer, characterized in that, The patterned copper pad surface is provided with an array of multiple micro-necked copper pillars. Each micro-necked copper pillar includes a lower base section, a necked section, and an upper base section in sequence from bottom to top along the axial direction. The lower base section is integrally connected to the patterned copper pad. The cross-sectional area of ​​the necked section is smaller than that of the lower base section and smaller than that of the upper base section. The upper base section is in contact with the nano-silver paste layer, so that when the micro-necked copper pillar is subjected to an axial pressure exceeding the yield pressure of the necked section, it undergoes axial plastic compressive deformation in the necked section. A radial microgroove network is provided in the gap area between adjacent micro-necked copper pillars. The radial microgroove network includes multiple microgrooves that extend radially outward from the center of the patterned copper pad. The outer end of each microgroove is connected to an annular gas collection groove provided around the patterned copper pad. A limiting solder resist dam is provided circumferentially around the patterned copper pad, and the inner sidewall of the limiting solder resist dam forms an angle of 30° to 45° with the plane where the patterned copper pad is located.

2. The packaging structure according to claim 1, characterized in that, The cross-sectional area of ​​the necked section decreases and then increases from the lower base section to the upper base section, giving the micro-necked copper column a dumbbell-shaped profile.

3. The packaging structure according to claim 1, characterized in that, The annular gas collecting groove is connected to the vacuum extraction passage of the sintering equipment, forming an exhaust path that runs through the center of the patterned copper pad to the external vacuum system.

4. The packaging structure according to claim 1, characterized in that, The limiting solder resist dam is continuously arranged around the periphery of the patterned copper pad to limit the lateral overflow range of the nano silver paste layer during the heated flow stage.

5. The packaging structure according to claim 1, characterized in that, Multiple micro-necked copper pillars are arranged in an array on the surface of the patterned copper pads. The axial plastic compression deformation of the micro-necked copper pillars in the necking section varies in the pad area corresponding to chips of different thicknesses, which is used to compensate for the thickness tolerance between adjacent chips.

6. The packaging structure according to claim 4, characterized in that, Guided by the inclination angle of the inner wall of the limiting solder resist dam, the nano-silver paste layer forms a concave meniscus structure with a rounded transition at the edge of the patterned copper pad.

7. A nano-silver sintering encapsulation process for high-power modules, used to prepare the encapsulation structure according to any one of claims 1 to 6, characterized in that, include: The ceramic copper-clad substrate with the micro-necked copper pillars, the radiating micro-groove network and the limiting solder resist dam on its surface is cleaned and surface activated, and a nano silver paste layer is coated on the surface of the patterned copper pads. The power chip is mounted on the nano-silver paste layer to complete the multi-chip array arrangement; The mounted ceramic copper-clad substrate is placed into the vacuum nano-silver sintering press chamber, the chamber temperature is raised to a first temperature, and a vacuum micro-pressure is applied to the chamber and maintained for a first time, which is 20 minutes. The organic gas volatilized in the chip area is discharged along the radiation micro-groove network to the annular gas collection groove, and then discharged from the chamber through the vacuum pumping passage. The cavity temperature is raised to a second temperature, and the application method is switched from vacuum micro-pressure to positive pressure loading. Positive pressure is applied and maintained for a second time, which is 30 minutes. This causes the necked section of the micro-necked copper column to undergo axial plastic compression deformation under pressure. At the same time, the nano-silver paste layer is densified and, under the restriction of the limiting solder resist dam, it climbs along its inner sidewall to form a concave meniscus structure. The cavity temperature is reduced to room temperature according to the preset cooling curve, and the positive pressure is released to normal pressure simultaneously. The sintered module substrate is then removed.

8. The packaging process according to claim 7, characterized in that, The first temperature is 150℃.

9. The packaging process according to claim 7, characterized in that, The second temperature is 250°C, and the applied positive pressure is 15 MPa.

10. The packaging process according to claim 7, characterized in that, After the sintered module substrate is removed, it is subjected to visual inspection and porosity testing.